2001
DOI: 10.2337/diacare.24.2.308
|View full text |Cite|
|
Sign up to set email alerts
|

Once- and Twice-Daily Dosing With Rosiglitazone Improves Glycemic Control in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -To determine the efficacy of rosiglitazone compared with placebo in reducing hyperglycemia. RESEARCH DESIGN AND METHODS-After a 4-week placebo run-in period, 959 patients were randomized to placebo or rosiglitazone (total daily dose 4 or 8 mg) for 26 weeks. The primary measure of efficacy was change in the HbA 1c concentration. Approximately 33% of drug-naive patients treated with rosiglitazone achieved HbA 1c Յ7% at study end. The proportions of patients with at least one adverse event were compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
159
3
7

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(189 citation statements)
references
References 27 publications
20
159
3
7
Order By: Relevance
“…Among those, the thiazolidinedione (TZD) class of drugs is currently used for the treatment of type 2 diabetes (28). They normalize glycemia and decrease insulin as well as free fatty acid serum levels in type 2 diabetic rodents and human subjects (29,30) and reduce atherosclerosis in certain mouse models (11).…”
mentioning
confidence: 99%
“…Among those, the thiazolidinedione (TZD) class of drugs is currently used for the treatment of type 2 diabetes (28). They normalize glycemia and decrease insulin as well as free fatty acid serum levels in type 2 diabetic rodents and human subjects (29,30) and reduce atherosclerosis in certain mouse models (11).…”
mentioning
confidence: 99%
“…Rosi is a potent antidiabetic drug which improves insulin sensitivity and glycaemic status (Phillips et al, 2001). In addition, it was shown that pretreatment with Rosi and other TZDs leads to the reduction of the adipocyte cell size (Johnson et al, 2007;Velebit et al, 2008).…”
Section: Rosiglitazone Increases the Plasma Membrane Glut4 Density VImentioning
confidence: 99%
“…However, with rosiglitazone it should be noted that 4 mg twice daily may be more potent than 8 mg once daily. 32 Lastly, it should be realized that it takes more time for the TZDs to demonstrate full effect than the other oral agents (3 to 4 months vs. several weeks). 32,33,36 Combination agents Within the last 2 years several combination agents have been released for use in the management of type 2 DM.…”
Section: Important Management Issues In Type 2 Dmmentioning
confidence: 99%
“…Interestingly, this alteration of gene transcription takes place in adipocytes and the genes concerned primarily regulate fatty acid metabolism, the net result of which is to decrease serum FFA by approximately 20% to 40%. [32][33][34] This reduction in FFA, in turn, improves insulin action in muscle tissue, thus implicating elevated FFA as a major contributor to insulin resistance. Further-more, this reduction in FFA improves β-cell function by decreasing lipotoxicity, a process whereby increased FFA eventually leads to β-cell death.…”
Section: Thiazolidinediones (Tzd)mentioning
confidence: 99%
See 1 more Smart Citation